Pathogenic SPTBN1 variants cause an autosomal dominant neurodevelopmental syndrome - Cousin, Margot A.; Creighton, Blake A.; Breau, Keith A.; Spillmann, Rebecca C.; Torti, Erin; Dontu, Sruthi; Tripathi, Swarnendu; Ajit, Deepa; Edwards, Reginald J.; Afriyie, Simone; Bay, Julia C.; Harper, Kathryn M.; et al. (Nature genetics, 2021)
SPTBN1 encodes βII-spectrin, the ubiquitously expressed β-spectrin that forms micrometer-scale networks associated with plasma membranes. Mice deficient in neuronal βII-spectrin have defects in cortical organization, developmental delay and behavioral deficiencies. These phenotypes, while less severe, are observed in haploinsufficient animals, suggesting that individuals carrying heterozygous SPTBN1 variants may also show measurable compromise of neural development and function. Here we identify heterozygous SPTBN1 variants in 29 individuals with developmental, language and motor delays; mild to severe intellectual disability; autistic features; seizures; behavioral and movement abnormalities; hypotonia; and variable dysmorphic facial features. We show that these SPTBN1 variants lead to effects that affect βII-spectrin stability, disrupt binding to key molecular partners, and disturb cytoskeleton organization and dynamics. Our studies define SPTBN1 variants as the genetic basis of a neurodevelopmental syndrome, expand the set of spectrinopathies affecting the brain and underscore the critical role of βII-spectrin in the central nervous system. SPTBN1 mutations cause a neurodevelopmental syndrome characterized by intellectual disability, language and motor delays, autism, seizures and other features. The variants disrupt βII-spectrin function and disturb cytoskeletal organization and dynamics.